Adoption of Mobile Learning: The Influence And Opportunities For Learning During The Covid-19 Pandemic - Pebriantika, Leni; Wibawa, Basuki; Paristiowati, Maria (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Research It is designed using quantitative and qualitative approaches. The sampling technique used in this study was purposive sampling. The samples in this study were lecturers and students. Data collection techniques using questionnaires and interviews. Interviews were conducted by interviewing lecturers at several different campuses. The results of the interview show that mobile learning is the learning that students are most interested in because it can be accessed through their cellphones. Quantitative data analysis used the product-moment correlation test. The research subjects consisted of 110 students. The significance level of 0.001 (p <0.05) indicates that there is a significant influence between the adoption of mobile learning on student interest in learning during the Covid pandemic 19.